2019
DOI: 10.1111/anae.14904
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Airway Society guidelines for awake tracheal intubation (ATI) in adults

Abstract: Summary Awake tracheal intubation has a high success rate and a favourable safety profile but is underused in cases of anticipated difficult airway management. These guidelines are a comprehensive document to support decision making, preparation and practical performance of awake tracheal intubation. We performed a systematic review of the literature seeking all of the available evidence for each element of awake tracheal intubation in order to make recommendations. In the absence of high‐quality evidence, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
348
0
24

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 315 publications
(427 citation statements)
references
References 168 publications
3
348
0
24
Order By: Relevance
“…This includes utilisation of cognitive aids such as checklists, cross-checking and pre-planned and explicitly defined airway management strategies [36]. Any airway management procedure should be managed electively should guide clinicians to determine the safety of asleep tracheal intubation, rather than awake tracheal intubation (ATI) [37,38]. Clinicians must note that ATI is potentially a highly aerosol-generating procedure, thus the decision to undertake ATI must be carefully considered.…”
Section: Airway Managementmentioning
confidence: 99%
“…This includes utilisation of cognitive aids such as checklists, cross-checking and pre-planned and explicitly defined airway management strategies [36]. Any airway management procedure should be managed electively should guide clinicians to determine the safety of asleep tracheal intubation, rather than awake tracheal intubation (ATI) [37,38]. Clinicians must note that ATI is potentially a highly aerosol-generating procedure, thus the decision to undertake ATI must be carefully considered.…”
Section: Airway Managementmentioning
confidence: 99%
“…In our study, 62% of anaesthesiologists in anaesthesia performed awake FOI ≤4 times yearly, which is more frequent than among the members of The Difficult Airway Society, where a recent survey demonstrated that 92% of the anaesthesiologists performed awake FOI ≤5 times yearly . Awake FOI should be an option in all departments day‐and‐night, which effectively mandates all anaesthesiologists to maintain their skills lifelong despite the limited training opportunities identified in both our study and many previous studies …”
Section: Discussionmentioning
confidence: 41%
“…19 Awake Tracheal Intubation should be performed in accordance with the Difficult Airway Society guidelines. 20 Different considerations apply when managing extrathoracic and intrathoracic airways. Lesions of the subglottis and the cervical trachea may be accessed via suspension laryngoscopy and are amenable to jet ventilation or THRIVE.…”
Section: Patient Managemementmentioning
confidence: 99%